Local Adaptation to Extreme Weather and It’s Implication on Sustainable Rice Production in Lampung, Indonesia - Dulbari Dulbari; Edi Santosa; Yonny Koesmaryono; Eko Sulistyono; Anung Wahyudi; Herdhata Agusta; Dwi Guntoro (AGRIVITA, Journal of Agricultural Science, 2021)
Extreme weather incidents refer to high rainfall and strong winds have been speculated to be detrimental on rice production. However, researches on the local adaptation to their impact on rice production are limited especially on tropical region like Indonesia. A study was conducted in Pesawaran, West Lampung, North Lampung, and Bandar Lampung using time series data of 2000-2015 and ground checking during extreme weather and normal seasons and its implication on sustainable management. Data were evaluated using multivariate regressions. Results demonstrated that the impact of extreme weather on the reduction of rice production was weak, 0.92%. Shifting on rice production among swampy, irrigated, and dry lands at which covered area of 13.67%, 42.69% and 43.65%, respectively, minimized the impact of the extreme weather. During limited precipitation, irrigated and swamplands had 2.5-3.0 times cropping intensity. Conversely, during La-Nina with excess precipitation, cropping in irrigated and drylands increased by 20 and 58%, respectively. Moreover, the local government maintained annual production improvement by about 5% through expansion of irrigated land, high yielding varieties and inputs subsidies. Considering that incident of extreme weathers tended to occur more frequently, consequently, planting calender utilization and rice variety adapted should be implemented.